Routledge handbook of celebrity studies - Elliott, Anthony 1964- (Routledge international handbooks, 2018)
Ours is the age of celebrity. An inescapable aspect of daily life in our media-saturated societies of the twenty-first century, celebrity is celebrated for its infinite plasticity and glossy seductions. But there is also a darker side. Celebrity culture is littered from end to end with addictions, pathologies, neuroses, even suicides. Why, as a society, are we held in thrall to celebrity? What is the power of celebrity in a world of increasing consumerism, individualism and globalization?